Live-in Relationship and Child Health in India: A Judicial Perspective (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The rise of live-in relationships in India has sparked significant debate and necessitated judicial intervention, particularly concerning the health and welfare of children born out of such unions. This research article delves into the legal framework governing live-in relationships, explores the judiciary's role in safeguarding child health, and examines the societal implications of these judicial decisions. Through a critical analysis of landmark cases and legislative developments, the article highlights the evolving nature of family law in India and its impact on child health in the context of live-in relationships.